Moving Toward 2050: Supplementing Traditional Nutrition Programs with 21st Century Training (P07-008-19). (13th June 2019) - Ringling, Keagan; Jansma, Melissa; Liffrig, Therese; Marquart, Len
Abstract: Objectives: Climate change, malnutrition, acute and chronic diseases nested within diverse sociocultural problems challenge nutrition professionals entering the workforce. Undergraduate and graduate education is a critical period to develop a foundation of transdisciplinary, transcultural and transformational approaches to understand and effectively use science to solve problems and manage issues in the 21st century. Employers seek multidisciplinary-trained individuals with critical thinking, communication, collaboration, and creativity to solve complex problems within continuously evolving adaptive systems. New training models are required to develop additional interactive skills integrated within a traditional nutrition program. Methods: To supplement traditional learning goals documented by Bloom's taxonomy, hands-on experiences were designed to achieve learning objectives based on key character attributes and professional skills including critical thinking, communication, collaboration, and creativity. The case consisted of 8 activities, with 7 goals, and 17 objectives. Activities gradually and dynamically built on preceding competencies of required goals and objectives. Results: The student participated in activities including non-profit civic engagement; a non-profit internship; a corporate quality assurance internship; an industry research fellowship; student clubs; student government advocacy; departmental engagement; and honors course development. The student developed: technical skills along with critical thinking, communication, collaboration, and creativity via internships and guided research; key character attributes through student government advocacy and student club participation; moral and ethical compass via departmental engagement and non-profit civic engagement; and creativity and systems thinking via honors course development. Conclusions: Developing dynamic human capacity to address systems issues is imperative to enhance the health of our society and planet. A comprehensive, holistic training program might allow students to directly participate in developing new workforce approaches and models. This pilot study serves as one example of a complimentary training program to equip students with skills to fulfill 21st century workforce requirements. Funding Sources: None.